Wybrane zagadnienia dotyczące słuchu dzieci = Selected issues concerning hearing children - Szymańska, Grażyna (Zielona Góra ; Skarbona: Stowarzyszenie Polskich Muzyków Kameralistów)
The problem of hearing children is of interest to many scientific disciplines. These are mainly medicine-clinical audiology, psychology and pedagogy. Some of them deal with hearing impairments, people with impaired hearing and other areas are important impact teaching and educational both for children with a healthy and hearing impaired.
Keywords: narząd słuchu; zaburzenie słuchu; słuchanie; słyszenie; lateralizacja słuchowa; wychowanie słuchowe; obiektywne metody badania słuchu; subiektywne metody badania słuchu; organ of hearing; impaired hearing; listening; hearing; auditory laterality; auditory education; objective methods of hearing tests; subjective test methods for hearing